Does Dynamic Downscaling Modify the Projected Impacts of Stabilized 1.5°C and 2°C Warming on Hot Extremes Over China? - Jun Ge; Bo Qiu; Runqi Wu; Yipeng Cao; Weidan Zhou; Weidong Guo; Jianping Tang (Geophysical Research Letters)
Abstract Using Weather Research and Forecasting (WRF) model, we perform the first dynamic downscaling of Community Earth System Model (CESM) Low‐Warming simulations to examine hot extreme changes over China in response to stabilized 1.5°C and 2°C global warming. WRF projects more intense and frequent hot extremes due to global warming, which are qualitatively consistent with CESM. However, WRF and CESM significantly differ in magnitudes of hot extreme changes. Compared to CESM, WRF indicates larger increases in hot extremes over Tibetan Plateau but smaller increases over other regions. Such differences between WRF and CESM are mainly caused by divergent projections of shortwave radiation changes. WRF also suggests fewer benefits achieved from the additional 0.5°C warming constraint than CESM. This study demonstrates the climate risks might be inadequately informed by global climate models and it is necessary to reevaluate impacts of 1.5°C and 2°C global warming on regional climate based on regional climate models.